Elimination of ochratoxin A by lactic acid bacteria strains isolated from chickens and their probiotic characteristics - Kupryś-Caruk, Marta; Stefańska, Ilona; Chabłowska, Beata (Wydawnictwo Politechniki Łódzkiej, 2017)
The aim of the study was to evaluate the ability of lactic acid bacteria strains, isolated from the gastrointestinal tract of chickens, to eliminate ochratoxin A (OTA) in vitro and to investigate whether the mechanism of OTA reduction is adsorption or hydrolysis. The probiotic characteristics of the strains, such as their growth performance and synthesis of lactic acid at 42°C, inhibition of Salmonella spp. and Escherichia spp. growth and susceptibility to antibiotics, was also evaluated. Ochratoxin A reductions in MRS broth depended on the tested strain and ranged from 1% to 29%. The level of OTA reduction was higher at 30°C than at 37 and 42°C and there were no significance differences between OTA reduction obtained with live and heat-treated bacteria cells. The evaluation of probiotic characteristics showed that Pediococcus acidilactici KKP 879 was the strain with more potential to develop a probiotic culture for chickens.
Keywords: lactic acid bacteria; ochratoxin A; phenylalanine; probiotics; bakterie kwasu mlekowego; ochratoksyna A; fenyloalanina; probiotyki